19 Do clinical measures relate to running asymmetries in patients with achilles tendinopathy?. (April 2019) - Corrigan, Patrick; Silbernagel, Karin Grävare
Abstract : Introduction: Achilles tendinopathy is an overuse injury that commonly sidelines runners and has a reinjury rate of 44%. Aberrant loading patterns during the return-to-sports (RTS) phase may partially explain reinjury rates, but it remains unknown if clinical measures are associated with loading behaviors. Therefore, we aimed to establish relationships between side-to-side differences in running mechanics and side-to-side differences in clinical measures of pain, tendon structure, and calf muscle function. Materials and methods: 12 runners with Achilles tendinopathy were included (age:44±11 y; height:171±10 cm; mass:70±12 kg; VISA-A score:71±10; current mileage:40±29 km/wk). Participants completed a 7 min run at endurance pace (2.9±0.3 m/s) on an instrumented treadmill with retroreflective markers affixed to their lower extremities. After a 6 min familiarization period, marker trajectories and ground reaction forces were sampled. Sagittal plane ankle joint moments and powers were calculated and a musculoskeletal model was used to estimate Achilles tendon loads. Pain-pressure threshold, tendon geometry, and calf muscle endurance were measured bilaterally with algometry, ultrasound imaging, and the heel-rise endurance test, respectively. Results: Side-to-side differences in pain-pressure threshold were significantly related to side-to-side differences in Achilles tendon loading rate (r=0.62; p=0.03) and peak plantarflexion moment (r=0.58, p=0.05). Side-to-side differences in peak eccentric ankle joint power were significantly related to side-to-side differences in tendon thickness (r=0.59, p=0.04) and cross-sectional area (r=0.73; p=0.01). Side-to-side differences in calf muscle endurance was significantly related to Achilles tendon loading rate (r=0.64; p=0.03). Conclusion: Clinical measures of pain and calf muscle endurance relate to side-to-side differences in Achilles tendon loading rates during running, while tendon geometry relates to eccentric ankle joint power.